Impact of an inconclusive exercise stress echocardiogram on cardiovascular outcomes. (4th February 2022) - Cardoso, A; Lourenco, MR; Von Hafe, P; Dias, G; Pereira, T; Tinoco, M; Fernandes, M; Azevedo, O; Lourenco, A
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Exercise stress echocardiography (ESE) is used for the assessment of suspected or known coronary artery disease (CAD); however, a certain percentage of ESE studies are inconclusive. We aim to evaluate the prognostic impact of an inconclusive ESE on cardiovascular outcomes. Methods: Single-center retrospective study of consecutive patients (pts) who performed an ESE between 2018 and 2019 for diagnosis or stratification of CAD. All pts performed a symptom-limited Bruce protocol. ESE was considered inconclusive when 85% of age-predicted maximum HR was not reached. Primary endpoint was a composite of admission for acute coronary syndrome (ACS), coronary revascularization and cardiovascular death during the follow-up. Results: A total of 141 pts were included (76% male; mean age 60 ± 9 years). ESE was inconclusive in 51 (36%) pts, positive in 11 (8%) and negative in 79 (56%). The mean exercise time of pts with inconclusive ESE was 7 ± 2 minutes and 76% had normal functional capacity. Fatigue (25 pts; 49%) and lower extremities pain (11 pts; 22%) were the main reasons for ESE stopping. Five pts (10%) complained of chest pain during exam. Pts with an inconclusive ESE were more diabetic (inconclusive 43%, positive 9%, negative 13%; p=.001), had more chronic obstructive pulmonary disease (COPD) (14%, 0%, 2.5%; p=.026), performed more frequently the exam under beta blocker (BB) therapy (59%, 27%, 18%; p=.041) and had less ST-segment depression fulfilling electrocardiographic criteria for ischemia (10%, 64%, 27%, p<.001). Their functional capacity was worse than negative ESE pts (p<.001). During a median follow up of 22 months (IQR 15-27), 13 (9.2%) pts had the primary endpoint, including 5 pts (3.5%) with ACS. Pts with an inconclusive ESE had a lower incidence of the primary outcome than pts with a positive ESE and a higher incidence of events than pts with negative results (figure). In multivariate analysis, after adjusting for functional capacity and electrocardiographic criteria for ischemia, an inconclusive ESE was an independent predictor of the primary endpoint (HR 9.7, IC95% 1.1-87, 6 p= .042) Conclusions: The frequency of inconclusive ESE is not negligible (36%). These pts had more diabetes and COPD and performed the exam under BB therapy more frequently, highlighting the importance of proper patient selection. An inconclusive ESE was associated to a higher risk of cardiovascular events compared to negative ESE.